Analyzing determinants of environmental conduct in small and medium-sized enterprises: a sociotechnical approach - Fonseca, J.; Ferreira, F.; Pereira, L.; Govindan, K.; Meidute-Kavaliauskiene, I. (Journal of Cleaner Production, 2020)
People are increasingly concerned about environmental issues. This concern presents new challenges for companies and impels them to incorporate environmental sustainability into their business strategies. However, smaller companies, such as small and medium-sized enterprises (SMEs), have often been prevented from considering environmentally friendly investments beyond those legally required because these firms lack a holistic perspective on sustainability. They also have a limited perception of the interdependence of corporate, economic, and environmental business components. The long-term survival of SMEs could be significantly strengthened by a holistic understanding based on integrated methods that facilitate the identification and representation of determinants of environmental conduct. These methods would further help to enhance these companies’ competitive advantages. This study sought to use fuzzy cognitive mapping techniques and the system dynamics (SD) approach to carry out analyses of determinants of environmental conduct in SMEs. The results show that this dual methodology enriches the decision-making process as it enables SME managers and decision makers to anticipate and analyze the consequences of their environmental conduct decisions. The results were validated by both the department head and a board member of Portugal’s Regional Proximity and Licensing Department of the Institute for the Support of Small and Medium-sized Enterprises and Innovation (IAPMEI in Portuguese). Static and dynamic analyses were carried out to test and more fully develop the proposed framework.